Effect of GLP-1 Receptor Agonist on Ischemia Reperfusion Injury in Rats with Metabolic Syndrome - Marko Ravic; Ivan Srejovic; Jovana Novakovic; Marijana Andjic; Jasmina Sretenovic; Maja Muric; Marina Nikolic; Sergey Bolevich; Kirill Alekseevich Kasabov; Vladimir Petrovich Fisenko; Aleksandra Stojanovic; Vladimir Jakovljevic (MDPI AG, 2024)
Metabolic syndrome (MetS) represents an important factor that increases the risk of myocardial infarction, and more severe complications. Glucagon Like Peptide-1 Receptor Agonists (GLP-1RAs) exhibit cardioprotective potential, but their efficacy in MetS-related myocardial dysfunction has not been fully explored. Therefore, we aimed to assess the effects of exenatide and dulaglutide on heart function and redox balance in MetS-induced rats. Twenty-four Wistar albino rats with induced MetS were divided into three groups: MetS, exenatide-treated (5 µg/kg), dulaglutide-treated (0.6 mg/kg). After 6 weeks of treatment, in vivo heart function was assessed via echocardiography, while ex vivo function was evaluated using a Langendorff apparatus to simulate ischemia-reperfusion injury. Heart tissue samples were analyzed histologically, and oxidative stress biomarkers were measured spectrophotometrically from the coronary venous effluent. Both exenatide and dulaglutide significantly improved the ejection fraction by 3% and 7%, respectively, compared to the MetS group. Histological analyses corroborated these findings, revealing a reduction in the cross-sectional area of cardiomyocytes by 11% in the exenatide and 18% in the dulaglutide group, indicating reduced myocardial damage in GLP-1RA-treated rats. Our findings suggest strong cardioprotective potential of GLP-1RAs in MetS, with dulaglutide showing a slight advantage. Thus, both exenatide and dulaglutide are potentially promising targets for cardioprotection and reducing mortality in MetS patients.